An Attempt to Estimate the Impact of the Spread of Economic Flows on Latenian Urbanization1 - Filet, Clara (Frontiers in Digital Humanities, 2017)
Over a relatively short period between the end of the 4th and the middle of the 1st century BC, an unprecedented process of urbanisation developed in non-Mediterranean Europe. Among all the factors contributing to the rise of the first agglomerations possessing urban characteristics in this area, this article focuses on the role of commercial interactions. The ability of settlements to interact within the trade network is approached by modelling of interactions. The aim is to provide new material to estimate the extent to which this factor could have impacted the known hierarchy of settlements on the one hand, and its role in the development of the Latenian urbanisation process on the other hand.